IDENTIFICATION OF EFFECTIVE FERTILITY RESTORERS IN RICE UNDER TEMPERATE CONDITIONS OF KASHMIR VALLEY - A. Majid; S.A. Waza; N.R. Sofi; A.B. Shikari; G.A. Parray; D.A. Bano; M.A. Bhat; M.A. Ahangar; F.A. Mohiddin; Z.A. Dar; I.A. Jehangir (Journal of Animal and Plant Sciences, 2022)
Exploitation of hybrid vigour is one of the most important applications of genetics in agriculture. It has highly contributed to food security, without affecting the environment. The availability of effective restorer lines that combines well with the CMS lines for various agro-morphological traits, determines the success of hybrid rice technology under temperate conditions like Kashmir Valley. To identify the best performing lines of rice in different cross combinations, four CMS lines and 34 genotypes were characterized for various agro-morphological and fertility restoration related traits. Out of 136 crosses, 43 (31.6%) were found to show the fertility restoration and 30 (22.06%) were found to be partial restorers. Sixty-three (46.32%) cross combinations were found to be partial maintainers and no cross combination was found to exhibit the maintainer behaviour. The genotypes RL-2, RL-3 and RL-8 were found to show restoration across all the CMS lines. Analysis of variance indicated the existence of significant differences among the genotypes, revealing that sufficient variability is present for different traits. The maximum positive value of standard heterosis for grain yield was recorded in SKUA-7A × RL-3. The marker-based assay using Rf3 and Rf4 linked markers was also carried out to validate the genes responsible for fertility restoration. The genotypes RL-1, RL-2, RL-5, RL-9, RL-11 and RL-12 showed polymorphism with all the markers. Sixteen hybrids showed fertility restoration behaviour with all the markers as well as under the field condition. Among these, 8 fall in the class of top 10 heterotic hybrids in the present study. The heterotic hybrids were evaluated for grain and cooking quality features. Out of the top 10 heterotic hybrids evaluated, nine were of medium to short grain types and only one SKUA-19A × RL-5 was of long grain type. Heterotic hybrids along with their parents showed intermediate amylose content which is preferable.
Keywords: Hybrid rice; restorer lines; molecular markers; Rf3; Rf4; cooking quality